Frog : a story of life on Earth - Thomas, Isabel, 1979- (Bloomsbury Children's Books, 2026)
This illustrated nonfiction book introduces young readers to the origins of life on Earth and the development of the universe. Framed through the story of a frog, it explores topics including the formation of the Earth, evolution, and the diversity of life. Lyrical text and vivid illustrations provide a narrative that combines scientific information with imaginative storytelling.